2015
DOI: 10.1007/s12288-015-0548-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiopoietin Levels are Different in Acute and Chronic Myeloid Neoplasms: Angiopoietins do not only Regulate Tumor Angiogenesis

Abstract: Molecular balance between Angiopoietin-1 (Ang-1) and Angiopoietin-2 (Ang-2) has important effects in tumor angiogenesis. Ang-2 was shown to be elevated and proved to be a prognostic factor in acute myeloid leukemia (AML). To date studies revealed increased angiogenesis in bone marrows (BMs) of both myeloproliferative neoplasm (MPN) and AML patients. We conducted this study to demonstrate circulating levels of Ang-1 and Ang-2 in MPN patients since no data exists in literature. Thirty-three newly diagnosed MPN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In cancer patients, however, this expressional pattern of Ang-1 and Ang-2 is perturbed. The serum levels of Ang-2 in cancer patients increase and the ratio between Ang-1 and Ang-2 in circulation decreases significantly [28][29][30][31]. This alteration in Ang-1 and Ang-2 expressional patterns in cancer patients seems to be concordant with the well-defined functions of these two angiogenic factors described earlier.…”
Section: Dysregulation Of Angiopoietins In Cancersupporting
confidence: 83%
“…In cancer patients, however, this expressional pattern of Ang-1 and Ang-2 is perturbed. The serum levels of Ang-2 in cancer patients increase and the ratio between Ang-1 and Ang-2 in circulation decreases significantly [28][29][30][31]. This alteration in Ang-1 and Ang-2 expressional patterns in cancer patients seems to be concordant with the well-defined functions of these two angiogenic factors described earlier.…”
Section: Dysregulation Of Angiopoietins In Cancersupporting
confidence: 83%
“…Moreover, much higher serum Ang-2 levels in patients with LVSI might also reveal the fact that Ang-2 is a potential biomarker that can be used in the evaluation of staging. Although some evidence suggests that the expression of Ang-2 in tumor tissue indicates poor prognosis, only a few studies evaluated the levels of Ang-2 in circulation [46][47][48][49][50]. However, so far there has been no uniform conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Atesoglu et al . [ 30 ] and Karakurt et al . [ 20 ] demonstrated that the expression of Ang1 was reduced in AML and ALL patients, similar to the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a significantly increased expression of Ang2 in ALL patients compared to that observed in the control group. Numerous studies have been performed to evaluate the expression of this gene in hematological malignancies, all of which have shown an increase in patient Ang2 expression levels compared to the control group [ 20 , 23 , 30 - 32 ]. However, a study by Cheng et al .…”
Section: Discussionmentioning
confidence: 99%